Integrating Reading and Writing Instruction for Cultivating Students' Critical Thinking - Yudha Aprizani; Neneng Islamiah (Universitas Islam Negeri (UIN) Mataram, 2019)
This study aimed to cultivate students’ knowledge and skills imperative for the development of critical thinking. This research employed qualitative method to explore students’ critical thinking through an integrated instruction of reading and writing tomeasure the extent to which the students understood and afford to learn English in reading and writing skills. In this research, researchers collected the data based on three factors, namely treatment, person, and outcome factor. Treatment factor is a technique of collecting data by observing students through the process of reading and writing instruction in classroom. Person factor, on the other hand, is a technique of collecting data by observing students observed directly by the other researchers in the process of English learning in classroom.Last, outcome factor is a technique of collecting data by using an open-ended question in a questionnaire based on students’ achievement in learning English. The data were analyzed and interpreted to answer the research questions. Based on the result of the study, we found out that the integration of reading and writing enabled the instruction to construct students’ prior knowledge and critical thinking by organizing the appropriate task-based activities. The study also developed the teaching strategies to be more effective in language teaching.